Proceedings of the 5th International Conference on the Durability of Concrete Structures 2016
DOI: 10.5703/1288284316132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nano-CaCO3 on the Properties of Cement Paste: Hardening Process and Shrinkage at Different Humidity Levels

Abstract: The hardening process and volume stability of cement pastes with and without nano-CaCO 3 (NC) were studied through investigations on the setting time and shrinkage. Results showed that NC shortened the setting time of cement paste: the initial setting time decreased by 3.9 and 11.1% when 1 and 3% NC were added, and the finial setting times were shortened by 6.2 and 15.2%, respectively. The shrinkage of cement paste was compensated by NC, and the effect was more obvious as more NC was added into the cement past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It provides a much more consistent control of concrete flowability to be used in digital manufacturing (Chu et al, 2021). It also provides enhanced strength, while reducing shrinkage during hydration (Cai et al, 2016). Finally, it drastically reduces the loss of water at temperatures as high as 800 C (Salih et al, 2020).…”
Section: Other Mineral Additionsmentioning
confidence: 99%
“…It provides a much more consistent control of concrete flowability to be used in digital manufacturing (Chu et al, 2021). It also provides enhanced strength, while reducing shrinkage during hydration (Cai et al, 2016). Finally, it drastically reduces the loss of water at temperatures as high as 800 C (Salih et al, 2020).…”
Section: Other Mineral Additionsmentioning
confidence: 99%
“…Nanosilica resulted to be a cement hardening accelerator, while nanoalumina was identified as a retarder. As Cai et al [ 111 ] demonstrated, nano-CaCO 3 accelerates the hardening process and decreases the shrinkage, although a high curing humidity of the samples is needed to improve the durability of cement-based composites.…”
Section: Nanoinclusionsmentioning
confidence: 99%
“…The kinetics of cement hydration and thus its hardening can be altered by the addition of nanoparticles. Nano-CaCO 3 can be applied as an accelerator (and additionally at lower shrinkage) of the hardening development [ 150 ], while nanoalumina can be used as a retardation additive [ 151 ].…”
Section: Nanoinclusionsmentioning
confidence: 99%